The importance of the immunodominant CD8+ T cell epitope of Plasmodium berghei circumsporozoite protein in parasite- and vaccine-induced protection - Gibbins, MP; Müller, K; Glover, M; Liu, J; Putrianti, ED; Bauza, K; Reyes-Sandoval, A; Matuschewski, K; Silvie, O; Hafalla, JCR (American Society for Microbiology, 2020)
The circumsporozoite protein (CSP) builds up the surface coat of sporozoites and is the leading malaria pre-erythrocytic-stage vaccine candidate. CSP has been shown to induce robust CD8+ T cell responses that are capable of eliminating developing parasites in hepatocytes, resulting in protective immunity. In this study, we characterized the importance of the immunodominant CSP-derived epitope SYIPSAEKI of Plasmodium berghei in both sporozoite- and vaccine-induced protection in murine infection models. In BALB/c mice, where SYIPSAEKI is efficiently presented in the context of the major histocompatibility complex class I (MHC-I) molecule H-2-Kd, we established that epitope-specific CD8+ T cell responses contribute to parasite killing following sporozoite immunization. Yet, sterile protection was achieved in the absence of this epitope, substantiating the concept that other antigens can be sufficient for parasite-induced protective immunity. Furthermore, we demonstrated that SYIPSAEKI-specific CD8+ T cell responses elicited by viral-vectored CSP-expressing vaccines effectively targeted parasites in hepatocytes. The resulting sterile protection strictly relied on the expression of SYIPSAEKI. In C57BL/6 mice, which are unable to present the immunodominant epitope, CSP-based vaccines did not confer complete protection, despite the induction of high levels of CSP-specific antibodies. These findings underscore the significance of CSP in protection against malaria pre-erythrocytic stages and demonstrate that a significant proportion of the protection against the parasite is mediated by CD8+ T cells specific for the immunodominant CSP-derived epitope.